Final analysis of a phase II study of nivolumab in combination with ipilimumab for unresectable chemotherapy‐naive advanced melanoma. Issue 11 (18th August 2020) - Namikawa, Kenjiro; Kiyohara, Yoshio; Takenouchi, Tatsuya; Uhara, Hisashi; Uchi, Hiroshi; Yoshikawa, Shusuke; Takatsuka, Sumiko; Koga, Hiroshi; Wada, Naoko; Minami, Hironobu; Hatsumichi, Masahiro; Namba, Yoshinobu; et al.
Abstract: Nivolumab plus ipilimumab combination is currently one of the preferred regimens for advanced melanoma in recently updated clinical practice guidelines. However, the evidence on the efficacy of the combination for acral or mucosal subtypes remains less robust. This is the final analysis of a multicenter, open‐label, uncontrolled phase II study that investigated the long‐term efficacy and safety in treatment‐naive Japanese patients with advanced melanoma, including acral or mucosal subtypes, and subsequent therapy after discontinuation of the investigational agents. Patients received four doses of nivolumab (1 mg/kg i.v.) in combination with ipilimumab (3 mg/kg i.v.) at 3‐week intervals, followed by doses of nivolumab (3 mg/kg i.v.) at 2‐week intervals. The median follow‐up period was 20.8 months (range, 5.2–35.0). The centrally and locally assessed objective response rates were both 43.3% (13/30; 95% confidence interval [CI], 25.5–62.6). Median progression‐free survival was not reached (95% CI, 3.02–not reached), and median overall survival was also not reached (95% CI, 19.52–not reached). The 30‐month progression‐free survival and overall survival rates were 50.3% and 54.2%, respectively. No new safety concerns were detected. After discontinuation of the investigational agents, 83.3% of patients received some form of subsequent therapy including 43.3% of patients who received nivolumab monotherapy and 26.7% of patients who received radiotherapy. Of the four patients who discontinued the investigational agents because of immune‐related adverse events, two received subsequent therapy (nivolumab and ipilimumab, respectively) and the other two showed long‐term treatment‐free survival (659 and 590 days, respectively). Long‐term survival with nivolumab plus ipilimumab was observed in Japanese patients with melanoma including acral and mucosal subtypes, which is consistent with the CheckMate 067 study. Many patients continued to receive some form of treatment safely after stopping treatment with nivolumab plus ipilimumab.